High‐grade PanIN presenting with localised stricture of the main pancreatic duct: A clinicopathological and molecular study of 10 cases suggests a clue for the early detection of pancreatic cancer. Issue 2 (30th May 2018) - Yokode, Masataka; Akita, Masayuki; Fujikura, Kohei; Kim, Mi‐Ju; Morinaga, Yukiko; Yoshikawa, Seiichi; Terada, Takuro; Matsukiyo, Hiroshi; Tajiri, Takuma; Abe‐Suzuki, Shiho; Itoh, Tomoo; Hong, Seung‐Mo; et al.
Abstract : Aims: This study aimed to identify the pathological features of high‐grade PanIN that presents with imaging‐detectable abnormalities. Methods and results: Ten cases of isolated, main‐duct, high‐grade PanIN as the primary clinical presentation were identified. All patients presented with stenosis of the main pancreatic duct, with two being associated with extensive upstream duct dilatation (>5 mm in diameter). Pancreatic juice cytology suggested adenocarcinoma in all seven cases examined. In resected specimens, high‐grade PanIN was present chiefly in the main pancreatic duct, with longitudinal extension ranging between 3 and 40 mm in length (median = 18 mm). In four cases, in which hypoechoic or hypovascular masses were observed on imaging, radiopathology correlations suggested that they represented parenchymal atrophy and subsequent fibrosis around affected ducts, but not invasive malignancy. On immunohistochemistry, the loss of p16 expression was found in five (50%), p53 overexpression in two (20%) and loss of SMAD4 expression in none (0%). KRAS mutations were detected in nine cases, with two dominant clones being found in three by ultrasensitive droplet digital polymerase chain reaction, suggesting the genetic heterogeneity of dysplastic cells composing individual lesions. Mutant GNAS was also observed in one case. Conclusions: Isolated high‐grade PanIN may present with pancreatic duct stenosis. Therefore, intensive investigations including pancreatic juice cytology will be required for patients with unexplained pancreatic duct stenosis. The abnormal expression of p53 and SMAD4 is infrequent, while GNAS may be mutated in premalignant lesions mainly affecting the main pancreatic duct, similar to KRAS .